Exploring the link between large earthquakes and magma transport at the onset of the Mayotte volcano-seismic crisis - Morales-Yáñez, Catalina; Duputel, Zacharie; Rivera, Luis (Comptes Rendus. Géoscience)
The archipelago of Comoros was generally considered a moderately seismic region. However, since May 2018, unusual seismicity has been observed off the east coast of Mayotte Island. Following this increase of seismic activity, oceanographic campaigns led to the discovery of a new submarine volcano, indicating that the observed seismicity had a volcanic origin. In this study, we estimate Centroid Moment Tensor (CMT) solutions of $M_w\ge 5$ earthquakes of this sequence using 3D Green’s functions and analyze their non-double-couple (non-DC) components. Consistently with previous reports, our results indicate that seismicity migrated upward in May–June 2018 with an increasing number of non-DC events. We show that non-DC components observed in our solutions and previously published catalogs cannot correspond to dike opening or closing as the observed rupture durations suggest unrealistically large magma flow rates. Given that waveforms can be relatively well explained with pure-shear sources, we postulate that non-DC components are most likely artifacts due to unmodeled shallow structural heterogeneities. Most $M_w\ge 5$ earthquakes have a strike-slip mechanism consistent with the rupture of pre-existing faults loaded by the regional stress regime and triggered by the increment of stress produced by the upward magma transfer.